Efektivitas Media Leaflet, Video Animasi, dan Games Kartu dengan Pengetahuan dan Sikap Mengenai Hipertensi di Rengasdengklok - Shamita Aira; Ratih Kurniasari; Eka Andriani (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Introduction: Hypertensive disease is called the silent disease because the sufferer is not aware if he suffers from hypertension before checking blood pressure to health services. The prevalence of hypertension in West Java is 39.6%. Karawang Regency is included in West Java Province with hypertension sufferers ≥15 years in 2022 as many as 625,156 people, where Rengasdengklok District is in 6th position at 61.87%. This study aims to determine the effectiveness of leaflets, animated videos, and statement card games on knowledge and attitudes regarding hypertension in Rengasdengklok, Karawang Regency. Method: The research method is quantitative research with a cross-sectional design. The population of 30 respondents was grouped into three groups, namely media leaflets, animated videos, and statement card games. Results: For the analysis technique, the data used are univariate and bivariate analysis with the Wilcoxon test for data that is not normally distributed and Paired Simple T-Test for data that is normally distributed. For the media leaflet, animation video, and games based on the results of the Paired Simple T-test and Wilcoxon test, the knowledge variable obtained p-values of 0.604>0.05, 0.031<0.05, and 0.018<0.05 respectively. Conclusion: In conclusion, in this study there was a significant influence on respondents' knowledge before and after being given animated video media and statement card games, while there was no significant effectiveness on respondents' knowledge before and after being given leaflet media.